Correlations between synthetic conditions and catalytic activity of LaMO3 perovskite-like oxide materials (M: Fe, Co, Ni): The key role of glycine - Petr Zemlianskii; Daniil Morozov; Gennady Kapustin; Nikolai Davshan; Konstantin Kalmykov; Vladimir Chernyshev; Alexander Kustov; Leonid Kustov (ChemPhysMater)
Herein N2O decomposition over LaMO3 (M: Fe, Co, Ni) mixed oxides with perovskite structures has been optimized. The influence of the organic additive and the additive to (La3+ + Co2+) molar ratio on phase composition, particle aggregate size, textural properties, and catalytic activity of LaCoO3 has been determined for the first time. Glycine improved the phase purity of LaCoO3, enhanced the specific surface area and pore volume, and shifted the pore size distribution to the wider mesopore and macropore regions. LaCoO3 showed better activity than LaFeO3 and LaNiO3 owing to the greater reducibility of Co3+ and its large specific surface area, and correlations between the La3+:Co2+ molar ratio, particle aggregate size, pore volume for pores larger than 25 nm, and N2O decomposition activity for LaCoO3 have been determined. Changes in the LaCoO3 textural properties following catalytic experiments with 10% water vapor added to the feed have also been analyzed here-in.